Marketing Communication Strategy during Covid-19 on Tourism Attraction in Tamansari Village - Raseru, Inoke; Rosilawati, Yeni (Jogjakarta Communication Conference (JCC), 2023)
Indonesia’s tourism sector in 2021 has shown a significant increase. The number of visitors by domestic and foreign tourists has shown an increase as evidenced by data from the Central Statistics Agency. This certainly threatens all people who rely on the tourism sector as a livelihood. One of the provinces in Indonesia, namely the Special Region of Yogyakarta, has tried various things to restore the tourism economy in the area. This research used a qualitative descriptive approach with the focus on descriptive studies. Data was collected through in-depth interviews and documentation. The Data was collected through in-depth interviews with the Government Tourism Office of Yogyakarta, Head of Tourism Destination Attraction, and the Head of Tamansari Tourism Village. The used of qualitative on this research is to gain a deep understanding and different perspectives on the impact of Covid-19 on Tourism Attraction in Tamansari. This study will provide new sufficiency in marketing communication research. Implementing the 4Ps marketing mix and marketing strategies can be applied to attracting tourists to Tamansari Tourism Village. Research found that marketing communication using the 4Ps (product, price, place, and promotion) elements is an effective model in the Tamansari tourism village. During the pandemic, the product can be created as virtual tours, allowing people to continue enjoying the uniqueness of Tamansari. In addition, Tamansari tourism village was also recognizing the Pentahelix stakeholders’ model, in which the model’s five stakeholders are invited to discuss how to create a tourism destination successful. It will be of great if Tamansari can utilize all of the marketing tools especially for promotion to boost tourist interest in the Tamansari region.